Effect of pH and temperature on phytase and biomass production by submerged fermentation with Aspergillus niger var. phoenicis URM 4924 (Research, Society and Development, 2022)
The production of phytase and biomass (estimated by the ergosterol content) by submerged fermentation with Aspergillus niger var. phoenicis URM 4924 was studied. Experimental assays were carried under different conditions of pH (4.0 to 8.0) and temperature (25 to 35 ºC), and the influence of these variables on the responses was studied through a 22 central composite design and response surface methodology. Phytase and biomass production were strongly affected by the pH and temperature used during fermentation. Phytase activity was increased in up to 7.8-fold (from 1.04 to 8.09 U/mL) and the ergosterol content was increased in up to 38-fold (from 9.3 to 354.09 µg/mL). The maximum values of both responses were achieved when using pH 4.0 and 30 ºC. Good correlation (second-order fit, R2 = 0.9875) was found between the data obtained for phytase activity and ergosterol content, suggesting that the phytase production depends on the biomass formation. These results are of interest since they contribute for the development of an industrial process for phytase production with elevated yields by submerged fermentation.